Understanding the Inhibition of Mild Steel Corrosion by dianiline Schiff bases: a DFT investigation. - Salah Eddine Hachani (Acta Chimica Slovenica, 2018)
Quantum chemical calculations at DFT/B3LYP level of theory with 6-31G, 6-311G, and 6-311G(d,p) basis sets were done to correlate the inhibition of mild steel corrosion in 1 M H2SO4 by four dianiline Schiff bases namely N,N’-Bis(benzylidene)-4,4’-dianiline (DAA), N,N’-Bis (benzylidene)-4,4’-methylenedianiline (MDAA), N,N’ Bis(benzylidene)-4,4’-sulphonyldianiline (SDAA) and N,N’-Bis(benzylidene)-4,4’-oxydianiline (ODAA) with their electronic and structural properties. Quantum chemical parameters such as the EHOMO, ELUMO, energy gap (∆E), dipole moment (µ), global softness (σ), and global hardness (η) were calculated and discussed to provide valuable explanations for the reactivity and selectivity of the studied inhibitors. The results obtained showed a certain relationship to the experimental inhibition efficiency results earlier reported.